Factors influencing smallholder farmers’ bean production and supply to market in Burundi - Birachi, Eliud Abucheli; Ochieng, J.; Wozemba, D.; Ruraduma, Capitoline; Niyuhire, M.C.; Ochieng, D. (African Crop Science Society, 2011)
Common bean (Phaseolus vulgaris L) is a major staple food in Burundi; thus increasing its production and marketing has the potential for raising incomes of the farming households. In the country, bean outputs have been declining for decades, yet demand for the crop in East Africa has surged considerably. This study was conducted in Burundi to assess the determinants of quantity produced and marketed by smallholder farmers. A total of 380 farmers obtained through a multistage sampling technique, constituted the study sample. Constraints to production and supply of beans to markets include lack of productive assets, lack of improved varieties and inadequate use of fertilisers. Results with regard to these constraints indicate that a unit increase in the value of productive assets is likely to lead to about 10 percent increase in production of beans; while changing to improved bean varieties may increase production by 22%. In addition, a kilogram increase in fertiliser use is likely to raise bean quantities produced by about 10%. Constraints that affect quantities of beans marketed by farmers include levels of production and losses due to transport problems. Thus, an increase in quantity produced will lead to an almost 30% increase in marketed quantities, while reduction in transport losses will lead to an increase in marketed quantities by about 12%. However, an increase in quantity of beans stored for food will lead a reduction in marketed beans by about 19%, implying that storage of beans may not be targeted at the market but for food security purposes. Efforts that promote collective action among farmers while encouraging increasing the proportion of land under beans are likely to enhance bean production and consequently marketable surplus.